Measurement properties of attitudes towards creative persons questionnaire: a reliable tool for understanding attitudes towards creative persons - Ordóñez Camacho, Xavier; Romero Martínez, Sonia (Creativity Studies, 2022)
The 21st century is characterized by challenges and opportunities and become the century of creativity. This is because the individuals develop creative tools to confront the changes that they are living. In this sense the study of attitudes towards creative persons is relevant, especially in the education context, because it permits to develop intervention programs that foster better attitudes on teachers and students. For that reason, the main objective of this research is to develop a questionnaire that allows to measure the attitudes of university students towards creative persons, and, to gather evidence about its reliability and validity. This research was made through an instrumental analytical study, with a sample of students pertaining to several faculties of the Complutense University of Madrid, Spain. At first, exploratory factor analysis, with a random half of the sample, was made. Secondly, the previous structure was confirmed by confirmatory factor analysis. The results confirm the three-dimensional structure (behavioral, affective, and cognitive dimensions). The final model exhibits an optimal fit and adequate reliability. The proposed instrument is a valid and reliable measure of the attitudes of the university students towards the creative persons.